Surgical Treatment Results of Osteoporotic Bimalleolar Ankle Fractures in the Elderly - Nadir Özkayın; Kemal Aktuğlu (Türk Osteoporoz Dergisi, 2002)
Purpose: In this study, the results of 2 different sugical treatment methods used in bimalleolar ankle fractures in osteoprotic patients older than 70 have been assessed. Methods: 38 fractures of 38 patients- 24 female and 14 male, with an avarege age of 74 (70-81)- were assessed who were hospitalized between 1994-2000 because of bimalleolar ankle fracture. The mean of Singh Indexes of the patients was 2.1/6 (1/6-3/6). The cause of the fracture in all patients was simply falling down. In 17 of the patients, osteosynthesis was obtained by laterally plating for lateral malleolus and cancellous or malleolar screws for medial malleolus (Group I), and in 21 it was obtained by posteriorly plating for lateral malleolus and tension band technique for medial malleolus ( Group II). Results: The average follow-up period was 52 (18-90) months. In Group I, the avarage immobilization in cast was 6 (4-9) weeks, the radiological bone union was 11 (8-13) weeks, resuming former activity level took 20 weeks, average loss of 7∞(0-10) dorsiflexion, and 8∞(0-15) flexion were observed, and 7 patients were identified to require a walking stick. Due to irritation on the skin, 4 patients required early removal of some of the screws. In contrast, in Group II the avarage immobilization in cast was 8 weeks (7-10), the radiological bone union 11 (8-14) weeks, resuming former activity level took 18 weeks, average loss of 5∞(0-8) dorsiflexion, and 5∞(0-8) flexion were observed, and 7 patients were identified to require a walking stick. Conclusion: In this type of fractures, along with the joint acommodation the surgical treatment also allows patients resume social activity in a shorter period of time. However the insufficiency of the bone structure makes it hard to obtain this purpose. Possible complications enforce having more control on surgical rehabilitation. Posterior plating and tension band technique is far more beneficial due to their biomechanical characteristics. Therefore it is a method to be preferred in the case of osteoporotic patients.